A Comparative Assessment of Basel II/III and Solvency II - Gatzert, Nadine; Wesker, Hannah (Geneva Papers on Risk and Insurance-Issues and Practice, 2012)
In the course of creating a single European market for financial services and in the wake of two financial crises, regulatory frameworks in the financial services industry in the European Union have undergone significant change. One of the major reforms has been the transition from static rules-based systems towards principles-based regulation with the intent to better capture the risk situation of an undertaking. For insurance companies, the regulatory framework Solvency II is being finalised and is scheduled for implementation after 2013. At the same time, the regulatory regime for banking, Basel II, has been revised in response to the financial crisis; the new version is Basel III. The aim of this paper is to conduct a comprehensive and structured comparative assessment of Basel II/III and Solvency II in order to detect similarities and differences as well as the benefits and drawbacks of both regimes, which might be profitably addressed. The comparison is conducted against the background of the industries characteristics and the objectives of regulation.
WiSo-Import:2015-03-26:3055
Keywords: Solvency II; Basel II/III